Chitin Microneedles for an Easy‐to‐Use Tuberculosis Skin Test. Issue 3 (26th August 2013) - Jin, Jungho; Reese, Valerie; Coler, Rhea; Carter, Darrick; Rolandi, Marco
<x xml:space="preserve">Abstract</x> An easy‐to‐use tuberculosis skin test is developed with chitin microneedles that deliver purified protein derivative at the correct skin depth and result in a positive test in BCG‐immunized guinea pigs <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>